2009
DOI: 10.1155/2009/737282
|View full text |Cite
|
Sign up to set email alerts
|

Leukotrienes in Atherosclerosis: New Target Insights and Future Therapy Perspectives

Abstract: Atherosclerosis represents an important chronic inflammatory process associated with several pathophysiological reactions in the vascular wall. The arachidonic acid, released by phospholipase A2, is an important substrate for the production of a group of lipid mediators known as leukotrienes, which induce proinflammatory signaling through the activation of specific BLT and CysLT receptors. The interaction of these substances in the vascular wall determines important morphological alterations like the early lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 60 publications
0
31
0
2
Order By: Relevance
“…43,44 It modulates the chemotaxis of DCs from the skin to lymph nodes, 23 the only antigen-presenting cell capable of activating naive T lymphocytes. 3,4 Previous studies aimed at analysing the effect of LTC 4 showed increases in the production of IL-10 by allergen-pulsed DCs, favouring their capacity to increase lung eosinophilia and IL-5 production in a model of murine asthma.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 It modulates the chemotaxis of DCs from the skin to lymph nodes, 23 the only antigen-presenting cell capable of activating naive T lymphocytes. 3,4 Previous studies aimed at analysing the effect of LTC 4 showed increases in the production of IL-10 by allergen-pulsed DCs, favouring their capacity to increase lung eosinophilia and IL-5 production in a model of murine asthma.…”
Section: Discussionmentioning
confidence: 99%
“…CysLT1 recombinant receptor is activated by all of the native ligands with the following order of potency: LTD4 > LTC4 > LTE4. In contrast, the agonist rank order potency for the CysLT2 receptor is LTD 4 = LTC 4 , with LTE 4 demonstrating less potency [10].…”
Section: Introductionmentioning
confidence: 93%
“…Mast cells preform and store approximately 500 secretory granules and many others which are made de novo and are released locally and in systemic circulation when specific antigens react major vasocostricting substance [61]. Leukotrienes are also powerful vasoconstrictors and their biosynthesis is enhanced in the acute phase of unstable angina [62,63]. Thromboxane is a potent mediator of platelet aggregation with vasoconstricting properties [64,65] and PAF, in myocardial ischemia, acts as proadhesive signaling molecule via activation of leukocytes and platelets to release leukotrienes or as a direct vasoconstrictor [66].…”
Section: Pathogenesismentioning
confidence: 99%